2016
DOI: 10.31381/revista_ciencias.v11i0.565
|View full text |Cite
|
Sign up to set email alerts
|

Abundancia, Frecuencia Y Distribución De Eufausidos Frente a La Costa Norte Del

Abstract: Se analizó la distribución, abundancia y frecuencia de eufáusidos de la costa norte del mar del Perú, desde Punta Sal (4°S) hastaHuarmey (10°S) durante el verano 2011-12 a bordo del RV Kaiyo Maru. Las muestras se colectaron mediante una Red Bongo operada en arrastres oblicuos desde 30m de profundidad hacia la superficie con barco en movimiento, provista con mallas de 350 micras de abertura. Se determinaron 5 especies y 3 hasta nivel de género, siendo la más abundante Euphausia mucronata con una abundancia rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Regarding euphausiids, certain species such as Euphausia mucronata, Euphausia eximia, and Euphausia lamelligera maintained their typical spatial distribution, spanning from Talara to Ilo for the first two species and from Talara to Chicama for the latter. Nevertheless, in the summer of 2020, E. mucronata exhibited a closer proximity to the coastal area (Orosco, 2023b). In contrast, in 2022, its distribution extended from the shelf break outward, resembling the pattern observed in spring 2019 (Orosco, 2023a).…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…Regarding euphausiids, certain species such as Euphausia mucronata, Euphausia eximia, and Euphausia lamelligera maintained their typical spatial distribution, spanning from Talara to Ilo for the first two species and from Talara to Chicama for the latter. Nevertheless, in the summer of 2020, E. mucronata exhibited a closer proximity to the coastal area (Orosco, 2023b). In contrast, in 2022, its distribution extended from the shelf break outward, resembling the pattern observed in spring 2019 (Orosco, 2023a).…”
mentioning
confidence: 61%
“…In contrast, in 2022, its distribution extended from the shelf break outward, resembling the pattern observed in spring 2019 (Orosco, 2023a). This shift was attributed to the projection of ccw away from the coast (Orosco & Ayón, 2015). In the case of E. distinguenda, its distribution along the maritime coast was limited to Callao, not extending to Ilo (further south) as in other seasons (summer 2016, 2019, 2020, and spring 2019) (Pinedo, 2022;Pinedo & Ayón, 2023;Orosco, 2023aOrosco, , 2023b).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The progressive latitudinal increase in the abundance of adults of E. mucronata coincides with the decrease in temperature; it is a trend previously reported for this species in coastal areas of the HCS (Mujica & Pavez 2008). Fernández et al (2002) found in the Mejillones area (23°S) an inverse relationship between adults abundance and temperature (El Niño vs. (Orosco & Ayón 2015). The significant predominance of adults over the other development stages would be a consequence of the sampling season (austral summer) and also likely the Bongo net sampling bias.…”
Section: Discussionmentioning
confidence: 96%